2021
DOI: 10.1055/a-1586-5493
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis and Prognosis of Fetuses with Bilateral Enlarged, Hyperechogenic Kidneys: Renal Volume and Amniotic Fluid Volume with Advancing Gestation

Abstract: Introduction This study’s objective was to identify prenatal criteria helping differential diagnosis of bilateral enlarged, hyperechogenic kidneys, especially looking at development of renal volume and amniotic fluid volume with increasing gestational age. Method Retrospective analysis (single-center database) of all bilateral enlarged, hyperechogenic kidneys between 2000–2018. Renal enlargement was defined as renal volume>90th percentile. Evaluation included development of renal and amniotic fluid volume d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
(30 reference statements)
0
13
1
Order By: Relevance
“…At initial presentation, 84.6% of fetuses with ARPKD showed oligo-or anhydramnios in our study, which is slightly higher than reported before (69-82%) [1]. In ARPKD, AF can further decrease during pregnancy or remain stable [25]. In contrast, fetuses with prenatal renal manifestations of ADPKD usually show normal amounts of AF [1,2] without tendency of progressive AF reduction [25].…”
Section: Amniotic Fluid (Af) Volumecontrasting
confidence: 58%
See 1 more Smart Citation
“…At initial presentation, 84.6% of fetuses with ARPKD showed oligo-or anhydramnios in our study, which is slightly higher than reported before (69-82%) [1]. In ARPKD, AF can further decrease during pregnancy or remain stable [25]. In contrast, fetuses with prenatal renal manifestations of ADPKD usually show normal amounts of AF [1,2] without tendency of progressive AF reduction [25].…”
Section: Amniotic Fluid (Af) Volumecontrasting
confidence: 58%
“…In ARPKD, AF can further decrease during pregnancy or remain stable [25]. In contrast, fetuses with prenatal renal manifestations of ADPKD usually show normal amounts of AF [1,2] without tendency of progressive AF reduction [25]. Similar to ARPKD, oligo-and anhydramnios from second trimester onwards are typical for RTD [5] and MKS [1,23].…”
Section: Amniotic Fluid (Af) Volumementioning
confidence: 99%
“…Retrieving articles according to predefined search terms, among the 311 Chinese and English articles identified, we eliminated 39 duplicate articles, 118 reviews, consensus and case reports, and 115 articles with irrelevant abstract and title, and finally selected the remaining 39 articles. After further research, a total of 21 articles (Decramer et al, 2007;Su et al, 2022;Li et al, 2007;Morr et al, 2022, Chaumoitre et al, 2006Digby et al, 2021;Mashiach et al, 2005;Estroff et al, 1991;Yulia et al, 2021;Shuster et al, 2019;Deng et al, 2022;Gilboa et al, 2016;Tsatsaris et al, 2002;Emmanuelli et al, 2010;Carr et al, 1995;Heidet et al, 2010;Zhang et al, 2017;Huang, 2014;Xie et al, 2022;Chen et al, 2022) were included in the final analysis (Figure 2; Table 4). Overall 1,178 cases arising from these studies were considered in the present meta-analysis.…”
Section: Results Of Literature Screening and Characteristics Of Inclu...mentioning
confidence: 99%
“…82 Kidney size near the upper limit of the normal range is a common finding in ADPKD, and the chance of having ADPKD increases linearly with renal volume enlargement above the 90th percentile in fetuses with normal amniotic fluid. 83 Oligohydramnios is observed in nearly 20% of cases of fetal ADPKD and is associated with a worse prognosis. 81 MRI is particularly indicated in antenatal diagnosis of ADPKD in atypical severe cases with oligohydramnios where the quality of US study is suboptimal 84 (Figure 7).…”
Section: Autosomal Recessive Polycystic Kidney Disease (Formerly Pott...mentioning
confidence: 99%
“…The increased cortical echogenicity is likely due to the presence of small microcysts that grow in size over time and typically form larger visible cysts after birth 82 . Kidney size near the upper limit of the normal range is a common finding in ADPKD, and the chance of having ADPKD increases linearly with renal volume enlargement above the 90th percentile in fetuses with normal amniotic fluid 83 . Oligohydramnios is observed in nearly 20% of cases of fetal ADPKD and is associated with a worse prognosis 81 …”
Section: Cystic Diseasesmentioning
confidence: 99%